The Cinema Cities Index: comparing urban cinema cultures around the world. Issue 1 (May 2017) - Coate, Bronwyn; Verhoeven, Deb; Davidson, Alwyn
[Cinema culture varies markedly around the globe and between cities. While this is obvious, the drivers of cinema culture are complex and interact in different ways across different locations and often give rise to a distinct character of localised cinema. This can be witnessed at different scales: across countries, between cities and, on a more granular level, based on localised neighbourhoods. In this article, we apply quantitative methods to investigate cities' ability to support cinema-going, or what we term 'cinemability'. We focus on four inter-related aspects that we argue contribute to a city's cinemability. These include the physical infrastructure of cinemas, the number and variety of films available, the presence of film festivals as a form of cultural signalling and the average cost of cinema admissions. In this article, we construct a ranked index of 'cinemability' based on data sourced from the Kinomatics Screen Dataset in order to facilitate a global comparison of contemporary cinema-going across 311 world cities. Our Cinema Cities Index is then compared with public contributions on the Cinema Cities website, http://www.cinemacities.com, where users can generate their own version of the index by assigning weights to the different variables based on their personal preferences. The results of our analysis reveal that the public place emphasis on factors such as the diversity of films offered and the affordability of cinema admission as key contributors to what makes a particular city amendable to 'cinemability'.